Improved composite open-hole compression strength and trade-off with manufacturability controlled by stacking sequence effect and non-standard ply angles. (1st January 2022) - Yu, Su; Yang, Yunpei; Colton, Jonathan S.
Abstract: The design of composite laminates requires consideration of part strength and manufacturability, both of which are controlled by ply angle and stacking sequence. This paper studies the open-hole compression strength and forming compatibility of laminates designed with standard angle (SA) and non-standard ply angle (NSA) layups using four different stacking sequence patterns. When increasing interply ply angle differences to provide greater interply lock-up, experimental test results show that dispersed stacking sequences improve failure strength of NSA laminates by up to 36%. Dispersed stacking patterns allow NSA laminates to consistently outperform reference SA laminates with increased failure strengths of up to 17%, indicating that this alternative design may produce stronger structural components. Results for stacking sequences of NSA laminates also reflect an inverse relationship between failure strength and formability. This implies an underlying trade-off between structural strength and manufacturing compatibility, which is worth considering when designing laminates for complex geometries. Highlights: Dispersed layups improve open-hole compression strength of non-standard angle laminates by up to 36%. Non-standard angle laminates with dispersed layups can outperform standard angle laminates on open-hole compression strength by up to 17%. Results show a trade-off between structural strength and manufacturing compatibility controlled by stacking sequence.